The Role Of Music In The Life Of Teenagers (Universitas Negeri Semarang, 2022)
Music is the expression of ideas, thoughts and feelings of the creator through the arrangement of tones or sounds to produce sound compositions in the form of songs. The purpose of this study was to determine the perception of adolescents on the role of music. The method/approach used in this study is a survey method using a questionnaire to 63 Indonesian teenagers with an age range of 10-24 years. The results showed that 45.3% of teenagers chose the pop genre as their favorite music genre to listen to and the majority of teenagers thought that pop genre music had a role as friends with activities with a percentage of 26.9%. Then 50% of teenagers' moods can be influenced by music. In conclusion, music has a very broad role in the lives of teenagers.